FEBI ONETOUCH: Efforts to Improve General and Academic Administration Services at the Faculty of Islamic Economics and Business, UIN RM Said Surakarta - Istilamah Laili; Muhammad Munadi (Relevance: Journal of Management and Business, 2023)
The global impact of Covid-19 pandemic has affected various aspects of life, including in world of education. Therefore, with the implementation of policies for online schools or lecturers, certainly there would also be a corresponding policy for online services. In order to facilitate administrative tasks for both students and lecturers, there is a necessity for an online-supported application, particularly with students population of approximately 4,000. Therefore, FEBI One Touch is an IT-driven application designed to increase both public and academic services within the Faculty of Islamic Economics and Business at UIN RM Said Surakarta. The research method used in this study is descriptive qualitative. In spite the mandatory of implementating FEBI One Touch, it has provided benefits for students and lecturers in terms of general and academic administrartion services. The challenges faced include unsupported mobile phones, users not being user-friendly, and the absence of operational service standards. In the end, it is expected that FEBI One Touch can be integrated with other incoming mail services and follow the standard operational procedures.